Diversity and distribution of Cirripedia from Gujarat Coast, India - Parmar, H. H.; Joshi, D. M.; Salvi, H.; Kamboj, R. D. (International Journal of Scientific Research in Biological Sciences, 2018)
Compared to other taxons of crustacea, limited literature is available on the diversity of Infraclass Cirripedia (Barnacles), as they are not much studied from the taxonomical point of view. The present study describes a total of 7 species of Intertidal cirripedia from Gujarat coast which includes the actual study and review. The highest species diversity was recorded from the Saurashtra coast bearing rocky intertidal areas, the highly supportive habitat for their attachment. The most common species observed were Tetraclita squamosa rufotincta, Amphibalanus amphitrite, Chthamalus stellatus and Balanus crenatus found flourishing on rocky shore with high density.